The Influence of Strategic Management Implementation, Stakeholder Pressure Mediated by Strategic Capabilities on the Sustainability of Organizational Performance - Afrianda, Rio; Zainal, Veithzal Rivai (Universitas Mercu Buana, 2025)
The incorporation of corporate programs that focus on sustainability strategies contributes to the balance between economic growth and the use of natural resources. This issue is not only limited to companies in developed markets but is also relevant for power generation companies that need to find ways to implement sustainable practices while improving organizational performance.In this context, the purpose of this study is to analyze whether strategic management can be considered as a strategic capability that contributes positively to the performance of power generation companies in Indonesia.To achieve this goal, we conducted a quantitative study through a survey, with data collected from 162 companies. Based on univariate and multivariate analysis, the results of the study indicate that strategic management can be considered as a strategic capability for power generation companies in Indonesia, because strategic management has a significant relationship with organizational performance.